Smart Nkunganire System user experience: insights & opportunities - Rabourn, T.; Simiyu, M.; Mudereri, B.T.; Senge, M.; Gatari, E.; Ogunsami, T.; Uzamushaka, S.; Sartas, M.; Kihoro, E.; Kangethe, E.; Muzata, B.S.; Guchu, W.; et al. (International Potato Center, 2024)
This report presents insights and opportunities to enhance the user experience of the Smart Nkunganire System (SNS), Rwanda’s digital agricultural input subsidy program. The methodology used to derive these findings employed a human centered design approach, gathering qualitative data from farmers, Sector Agronomists, and agro-dealers. Key findings highlight opportunities to enhance the SNS specifically for farmers as well as Sector Agronomists to ensure we achieve the anticipated adoption rate for tailored fertilizer recommendations. We conclude that farmers would benefit from clearer communication about the tailored nature of fertilizer recommendations. They would also benefit from using the SNS on their phones instead of relying on intermediaries because it would improve their understanding of the tailored recommendations. We also find that addressing network limitations and timing of orders is crucial for a smoother user experience. For Sector Agronomists, mobile-friendly solutions and continuing the digital transformation of their work would enhance efficiency and increase their confidence in the new system. Overall, the recommendations focus on making the SNS efficient, easy to use, reliable, and trusted to increase the adoption of tailored fertilizer recommendations.